دور السياسة الفلاحية في تحقيق التنويع الاقتصادي – دراسة قياسية لأثر القطاع الفلاحي على النمو الاقتصادي خلال الفترة1990-2020 باستخدام نموذج Ardl- - سويسي, صلاح الدين; جرفي, زكريا; الحاج, أحمد فوزي (جامعة الوادي - University of Eloued, 2023)
The financial allocations granted by the state in the framework of the agricultural reforms that it has adopted since the year 2000 through the funds it established to finance the implementation of the agricultural and rural development strategy, is one of the most important mechanisms to overcome the deficiencies recorded during this stage, which led to an increase in agricultural production, both plant and animal, Which allowed to increase the contribution of the agricultural sector to economic growth. This study aims to determine the short and long-term relationship between agricultural output as an independent variable, and the gross domestic product (economic growth) as a dependent variable during the period 1990-2020, using the ARDL Model. There is a problem of autocorrelation of the sequence of errors with the stability of estimations over time
The role of agricultural policy in achieving economic diversification – a standard study of the impact of the agricultural sector on economic growth during the period 1990-2020 using the ARDL model
مقال
Keywords: سياسة فلاحية ; نمو اقتصادي ; نموذج ARDL ; جزائر; agricultural policy; economic growth; ARDL model; Algeria